2002
DOI: 10.1021/tx020028j
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachloroethylene Oxide:  Hydrolytic Products and Reactions with Phosphate and Lysine

Abstract: Tetrachloroethylene, or perchloroethylene (PCE), has considerable industrial use and is of toxicological interest because of a variety of effects. Most of the existing literature presents PCE oxide as a critical intermediate in the oxidative metabolism of PCE to Cl(3)CCO(2)H, oxalic acid, and products covalently bound to proteins, including trichloroacetyl derivatives of lysine. PCE oxide was synthesized by photochemical oxidation of PCE and characterized. Decomposition at neutral pH (t(1/2) = 7.9 min at 0 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…​ Similarly, P450 2E1 converts tetrachloroethylene to an epoxide, which also breaks down through 1,2-chloride shift and hydrolytic pathways, leading to the formation of CO and CO 2 299 (Figure 84).…”
Section: C-c Bond Breaking Reactionsmentioning
confidence: 99%
“…​ Similarly, P450 2E1 converts tetrachloroethylene to an epoxide, which also breaks down through 1,2-chloride shift and hydrolytic pathways, leading to the formation of CO and CO 2 299 (Figure 84).…”
Section: C-c Bond Breaking Reactionsmentioning
confidence: 99%
“…Oxidation (Figure 1, left) occurs predominantly in the liver to a ferric-oxide (Fe-O) intermediate, the primary fate of which is thought to be trichloroacetyl chloride (TCAC), which then hydrolyses to yield trichloroacetic acid (TCA). A secondary fate of oxidation is the epoxide (PCE-O), which decomposes to ethandioyl dichloride (EDD) and then to carbon monoxide (CO) and carbon dioxide (CO 2 ) (Yoshioka et al 2002). Oxalic acid (OXA) has been reported as both an in vivo and in vitro product of PCE oxidation (Pegg et al 1979; Yoshioka et al 2002) and may be derived either from the epoxide or directly from the Fe-O intermediate.…”
Section: Role Of Metabolism In Pce Toxicitymentioning
confidence: 99%
“…A secondary fate of oxidation is the epoxide (PCE-O), which decomposes to ethandioyl dichloride (EDD) and then to carbon monoxide (CO) and carbon dioxide (CO 2 ) (Yoshioka et al 2002). Oxalic acid (OXA) has been reported as both an in vivo and in vitro product of PCE oxidation (Pegg et al 1979; Yoshioka et al 2002) and may be derived either from the epoxide or directly from the Fe-O intermediate. PCE conjugation with GSH (Figure 1, right) in the liver or kidney forms trichlorovinyl glutathione (TCVG), which is further processed by γ-glutamyl transpeptidase (GGT) and cysteinylglycine dipeptidase (DP) in the kidney, forming the cysteine conjugate S -trichlorovinyl- l -cysteine (TCVC).…”
Section: Role Of Metabolism In Pce Toxicitymentioning
confidence: 99%
“…49 The study also found that oxalyl chloride, the rearrangement product derived from perchloroethylene oxide, reacts not only with proteins but also with phosphate. The product, oxalyl phosphate, is relatively stable and can be isolated ( t 1/2 ~100 minutes); it does not react with proteins.…”
Section: E107mentioning
confidence: 94%
“…The product, oxalyl phosphate, is relatively stable and can be isolated ( t 1/2 ~100 minutes); it does not react with proteins. 49 These results are of interest given the large number of bioactivation studies that have been done using high concentrations of phosphate buffer (eg, 100 mM).…”
Section: E107mentioning
confidence: 99%